The Impact of Relationship Marketing on Customer Loyalty in the Banking Sector - Nor Aza, Maulad Musa (2009)
This research explores the impact of relationship marketing on customer loyalty in banking context. A survey of students of Universiti Utara Malaysia (UUM) and employees of Permintex Industries Sdn. Bhd was conducted to determine the significance and influence of the underpinnings of the relationship marketing such as trust, commitment, conflict handling, values and empathy on customers' loyalty in the banking sector. A total of 138 usable questionnaires were obtained from a total of 150 questionnaires distributed. The findings shows that the four (4) variables namely trust, conflict handling, values and empathy were important in determining and influencing customers' loyalty. Since the results of the research showed that customers' loyalty is related to trust, conflict handling, values and empathy factors, therefore banks need to consider these factors and provide the right tenant mixes, services, and other facilities that are essentials for attracting customers.